Інфляційний магнітогенез з гелікальним зв’язком - Shtanov, Yu. V.; Pavliuk, M. V. (Publishing house "Academperiodika", 2019)
We describe a simple scenario of inflationary magnetogenesis based on a helical coupling to electromagnetism. It allows the generation of helical magnetic fields with strength of order up to 10−7 Gs, when extrapolated to the current epoch, in a narrow spectral band centered at any physical wavenumber after the adjustment of model parameters. The additional constraints on magnetic fields arise from the considerations of baryogenesis and, possibly, from the Schwinger effect of the creation of charged particle-antiparticle pairs.